Coca-cola socialism : Americanization of Yugoslav culture in the sixties - Vučetić, Radina (Central European University Press, 2018)
This book is about the process of Americanization of Yugoslav culture and everyday life during the sixties. After having fallen out of the Eastern bloc, Tito turned to American backing. In political spheres distance was carefully guarded, yet in the realms of culture and consumption the Yugoslav regime was definitely much more receptive. For Titoist Yugoslavia this tactic turned out to be rewarding. It stabilised the regime internally and gave it an image of openness in foreign policy. The book addresses the link between cultural diplomacy, culture, consumer society and politics. The main argu.